Tributyltin chloride (TBTCL) induces cell injury via dysregulation of endoplasmic reticulum stress and autophagy in Leydig cells - Chen, Pengchen; Song, Yali; Tang, Li; Zhong, Wenbin; Zhang, JingJing; Cao, Min; Chen, Junhui; Cheng, Guangqing; Li, Huiying; Fan, Tianyun; Kwok, Hang Fai; Wang, Jigang; et al. (Journal of hazardous materials, 2023)
Tributyltin chloride (TBTCL), a commonly used antiseptic substance, is commonly found in the environment. Human exposure to TBTCL through the consumption of contaminated seafood, fish, or drinking water has aroused concern. It is well-characterized that TBTCL has multiple detrimental effects on the male reproductive system. However, the potential cellular mechanisms are not fully elucidated. Here, we characterized molecular mechanisms of TBTCL-induced cell injury in Leydig cells, a critical supporter for spermatogenesis. We showed that TBTCL induces apoptosis and cell cycle arrest in TM3 mouse Leydig cells. RNA sequencing analyses revealed that endoplasmic reticulum (ER) stress and autophagy were potentially involved in TBTCL-induced cytotoxicity. We further showed that TBTCL causes ER stress and inhibited autophagy flux. Notably, the inhibition of ER stress attenuates not only TBTCL-induces autophagy flux inhibition but also apoptosis and cell cycle arrest. Meanwhile, the activation of autophagy alleviates, and inhibition of autophagy exaggerates TBTCL-induced apoptosis and cell cycle arrest flux. These results suggest that TBTCL-induced ER stress and autophagy flux inhibition contributed to apoptosis and cell cycle arrest in Leydig cells, providing novel understanding into the mechanisms of TBTCL-induced testis toxicity. [Display omitted] •Tributyltin chloride induces apoptosis and cell cycle arrest in mouse Leydig cells.•Tributyltin chloride raises endoplasmic reticulum (ER) stress and impairs autophagy flux.•Disordered autophagy depends on the ER stress caused by TBTCL•Tributyltin chloride induced apoptosis and cell cycle arrest are mediated by autophagy process.